The Influence of Organizational Culture and Work Ethic against the Competence and Performance of Lecturers - Wairisal, Paulus L; S, Sahusilawane (Budapest International Research and Critics University, 2022)
This study aims to analyze and explain the direct influence of organizational culture on competence, the indirect influence of organizational culture on lecturer performance through competence. Analyze and explain the direct effect of work ethic on competence and indirect effect of work ethic on lecturer performance through competence. Analyze and explain the influence of competence on lecturer performance. The object of research at the Faculty of Teacher Training and Education, Pattimura University. Sampling _ as many as 72 respondents. The sampling technique is saturated sample. The analytical method used is path analysis with the help of SPSS 21. The results of this research descriptively, respondents' responses to organizational culture stated that they agreed with a mean value of 3.91. Respondents' responses to work ethic stated that they strongly agreed with a mean value of 4.32. The results of the hypothesis test prove that organizational culture with indicators: systems, norms, rules, beliefs, and shared expectations have a significant positive direct effect on competence. Significance value (0.027 < 0.05). Organizational culture has a significant positive indirect effect on lecturer performance through competence (0.031 < 0.05). The hypothesis is accepted. This shows that an organizational culture that is well implemented and adhered to by all individuals can improve competence as well as improve lecturer performance through competence. Work ethic with work indicators is grace, work is a calling, work is actualization, work is service, has a significant positive direct effect on competence. Significance 0.013 < 0.05. Work ethic has a significant positive indirect effect on lecturer performance through competence. Significant 0.019 <0.05. it shows that work ethic can increase competence and indirectly improve lecturer performance. The application of the work ethic must be maintained. Competence with indicators: Knowledge, skills, concepts, personal characteristics, motives have a significant effect on lecturer performance with indicators: loyalty, work performance, responsibility, obedience, honesty, cooperation and initiative. Significance value 0.003<0.005. If the competence is increased by one interval, the lecturer's performance will increase.